Report of 5 novel mutations of the α-L-iduronidase gene and comparison of Korean mutations in relation with those of Japan or China in patients with mucopolysaccharidosis I. Issue 1 (December 2016) - Kwak, Min; Huh, Rimm; Kim, Jinsup; Park, Hyung-Doo; Cho, Sung; Jin, Dong-Kyu
Abstract Background Mucopolysaccharidosis I (MPS I) is an autosomal recessive lysosomal storage disorder caused by a lack of the lysosomal enzyme α-L-iduronidase (IDUA). To date, more than 200IDUA mutations have been reported. However, only a few types of mutations are recurrent and the frequencies of mutations differ from country to country. Methods We performed theIDUA mutation analysis in seven patients who were biochemically diagnosed with MPS I in the Department of Pediatrics, Samsung Medical Center, from 2009 to 2014. Here, we describe the results of theIDUA mutation analysis in seven patients with MPS I and theIDUA mutational spectrum in Korean patients with MPS I, including previous data. Results TheIDUA mutations were found in all 14 alleles of 7 patients, and 11 kinds ofIDUA mutations were identified. The detected mutations were five missense mutations (p.A79V, p.L346R, p.T388K, p.P496R, and p.C577Y), two nonsense mutations (p.Y618* and p.R628*), two deletions (c.683delC and c.1591delC), one splice site mutation (c.972+1G>A), and one duplication (c.613_617dup). Among these, p.T388K, p.C577Y, c.683delC, c.1591delC, and c.972+1G>A were novel mutations that have not previously been reported. After taking everything into consideration, includingIDUA mutation analysis of the previously reported 10 unrelated Korean patients with MPS I, p.L346R and c.704ins5 were most commonly found in Korean patients with MPS I. However, p.W402* and p.Q70*, which have mainly been found in Caucasian patients, were not found. Conclusion As a result, p.L346R and c.704ins5, which were the most common in Korea, which is geographically situated midway between China and Japan, were some of the most common mutations in China and Japan, respectively. These results are especially worthy of notice.